Assessment of Nurses’ knowledge and Practices Concerning Hemodialysis Adequacy Guideline in Baghdad TeachingHospitals - Qusay M. Hadi; Jumma Alreda (Kufa Journal for Nursing Sciences)
Background: Kidney disease ranks third among life threatening diseases in the world, after cancer and heart disease, it goes about 200000.